2019
DOI: 10.1002/lary.28043
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Flap Oxygen Using Electron Paramagnetic Resonance Oximetry

Abstract: Objectives/Hypothesis To determine if electron paramagnetic resonance (EPR) oximetry is a viable technology to aid in flap monitoring. Study Design Prospective cohort. Methods This was a cohort study assessing accuracy and speed of EPR oximetry in detecting ischemia of a saphenous artery–based flap in a rat model, using transcutaneous oximetry as a control. Measurements were obtained under both resting and ischemic conditions for nine Sprague Dawley rats (18 flaps), for 3 postoperative days following flap elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The probe is being evaluated for permanent implantation under an US Food and Drug Administration investigational device exemption and can be removed via surgical resection, for example, during standard‐of‐care en bloc tumor resection 11 . We have shown, in preclinical models and human subjects, that EPR oximetry using the OxyChip is a practical method for measuring tissue pO 2 directly and repeatedly 3,6,12–23 . A phase I clinical study at Dartmouth‐Hitchcock Medical Center (Lebanon, NH) has confirmed that this technique can be applied to human subjects successfully, thus meeting a currently important but unmet need—the ability to make direct, repeated measurements of oxygen in tissue at specific anatomical sites 11,24 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The probe is being evaluated for permanent implantation under an US Food and Drug Administration investigational device exemption and can be removed via surgical resection, for example, during standard‐of‐care en bloc tumor resection 11 . We have shown, in preclinical models and human subjects, that EPR oximetry using the OxyChip is a practical method for measuring tissue pO 2 directly and repeatedly 3,6,12–23 . A phase I clinical study at Dartmouth‐Hitchcock Medical Center (Lebanon, NH) has confirmed that this technique can be applied to human subjects successfully, thus meeting a currently important but unmet need—the ability to make direct, repeated measurements of oxygen in tissue at specific anatomical sites 11,24 .…”
Section: Introductionmentioning
confidence: 93%
“…11 We have shown, in preclinical models and human subjects, that EPR oximetry using the OxyChip is a practical method for measuring tissue pO 2 directly and repeatedly. 3,6,[12][13][14][15][16][17][18][19][20][21][22][23] A phase I clinical study at Dartmouth-Hitchcock Medical Center (Lebanon, NH) has confirmed that this technique can be applied to human subjects successfully, thus meeting a currently important but unmet need-the ability to make direct, repeated measurements of oxygen in tissue at specific anatomical sites. 11,24 These studies also have provided useful information on some present limitations of EPR oximetry for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…This process is sensitive to the partial pressure of oxygen (pO 2 ) at the probe location, with the relaxation rate of the probe increasing as a function of pO 2 in the tissue adjacent to the probe (37,48). The OxyChip is an oxygen-sensing probe containing paramagnetic LiNc-BuO crystals embedded in PDMS for clinical applications (43)(44)(45)(46)(47). The OxyChips used in this study were of a cylindrical shape, 5 mm in length and 0.6 mm in diameter (Figure 1B).…”
Section: In Vivo Epr Oximetry With the Oxychipmentioning
confidence: 99%
“…One such oxygen-sensing paramagnetic material is lithium octa-butoxynaphthalocyanine (LiNc-BuO) crystals (40,42). An implantable oxygen probe, called the OxyChip, has been developed by embedding LiNc-BuO crystals in the oxygenpermeable polymer polydimethylsiloxane (PDMS) for pO 2 measurements (43)(44)(45)(46)(47). Embedding the LiNc-BuO in PDMS shields the crystals from interaction with the biological microenvironment, thereby preventing biochemical degradation and breakdown, as well as local and/or systemic interactions.…”
Section: Introductionmentioning
confidence: 99%